Measurement and reconstruction of geometric parameters of the barrel bore based on the laser scanning strategy - Zhang, Pengjun; Jin, Wei; Ren, Dongdong; Lyu, Yunfei (Frontiers in Physics, 2023)
The inner surface defects can be displayed intuitively by measuring the geometric parameters of rifling of the artillery barrel. In this paper, the parameters of the barrel bore were scanned based on high-precision laser, and the three-dimensional reconstruction of the bore shape was conducted based on the test data. The wavelet transform was used for multiple denoising of the test data, and the Delaunay triangulation interpolation algorithm was used to reconstruct the three-dimensional contour structure of the barrel bore, forming a high fidelity measurement strategy for the parameters of the barrel bore. The results show that this measurement strategy can achieve high-precision measurement of the geometric parameters of the barrel rifling, and the accuracy can reach 0.001 mm. By comparing the measured value of rifling with the standard value, the flaw points in the rifling of the birth tube can be accurately specified. The three-dimensional model reconstruction based on massive sample data realizes the high fidelity measurement of rifling geometric parameters. This measurement strategy can provide support for the visualization of barrel rifling and effectively improve the detection accuracy of barrel bore.